PEMANFAATAN FOLKLOR SENTANI SEBAGAI MEDIA PEMBELAJARAN LINGKUNGAN HIDUP DI SD NEGERI INPRES KLEUBLOUW, KAMPUNG HARAPAN, KABUPATEN JAYAPURA - Wigati Yektiningtyas; Papuana Pepuho; Monika Gultom (LPPM Uncen, 2021)
Flood often happens in Sentani, especially when heavy rains. Flood usually is related to people’s ignorance in preserving their environment, i.e. illegal logging, water and land pollution. Children as the future generation have to know how to respect and preserve nature. This inisiative is utilizing folklore as media to learn environmental preservation in SD Negeri INPRES Kleublouw using folktales, oral poems (ehabla) and traditional poverbs that are almost extinct. The objectives of the activities are (1) giving awareness about the importance of preserving natural environment, (2) motivating teachers and pupils about learning using local sources, (3) encouraging revitalization of Sentani cultural heritages. Both teachers and pupils of SDN INPRES Kleublouw were involved. From the activity, it is hoped that Sentani children and teachers have freedom in utilizing contextual sources not only as materials of teaching-learning and but also using them as media of relearning and disseminating Sentani folkore and all the socio-cultural values embedded in them.Keywords: folklore Sentani, environment, folktale, oral poems, traditional poverbs